2020
DOI: 10.3390/su12030956
|View full text |Cite
|
Sign up to set email alerts
|

Lean Tools, Knowledge Management, and Lean Sustainability: The Moderating Effects of Study Conventions

Abstract: It is essential for enterprises to develop lean sustainability. In this way, both the learning and understanding of the knowledge of lean tools becomes necessary. In fact, knowledge management plays a key role in the application of lean tools. In this paper, an in-depth exploration is carried out, investigating the mechanism of knowledge management which mediates between lean tools and the lean sustainability of enterprises, as well as the regulatory role of study conventions. Furthermore, a large sample from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Therefore, the lean philosophy already allows to support eco‐design already at the design stage, thus promoting a circular production model that improves, through RL, the recyclability of a product that is increasingly sustainable, less energy‐consuming, and based on secondary raw materials. Nonetheless, the lean‐sustainable production concept is still a new business strategy, without tangible feedback on its practical implementation (Abualfaraa et al, 2020; Zhang et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, the lean philosophy already allows to support eco‐design already at the design stage, thus promoting a circular production model that improves, through RL, the recyclability of a product that is increasingly sustainable, less energy‐consuming, and based on secondary raw materials. Nonetheless, the lean‐sustainable production concept is still a new business strategy, without tangible feedback on its practical implementation (Abualfaraa et al, 2020; Zhang et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, improving the productivity of the construction industry is a fundamental need for a more sustainable society. Various authors have indicated a useful link between Lean Construction and Sustainability [10][11][12], as it is necessary to ensure survival in a constantly evolving business environment, through a sustainable environment driven by Lean, with significant untapped potential [11]. Furthermore, organizations have recognized the need for an approach that contributes not only to the production of buildings but primarily to the delivery process and improvement in product quality as a whole [11].…”
Section: Need and Relevance Of Researchmentioning
confidence: 99%
“…However, despite this, a system of quantitative instruments or methodologies has not been developed to carry out a specific management of the quality of commitments. Furthermore, recent studies show how the application of Lean Construction has focused on social responsibility (external) and engagement of the work environment (internal), filling gaps that sustainable practices alone cannot fill [11], also demonstrating that the application of Lean tools has a direct positive impact on the sustainability of projects [12].…”
Section: Need and Relevance Of Researchmentioning
confidence: 99%